Al-based MOF derived self-assembled carbon nanosheets as innovative anodes for Li-and Na-ion batteries - Zeng, Xie-Rong; Wenwu, Jin; Li, Hejun; Saikumar, Inguva; Zhang, Qi; Shaozhong, Zeng; Guozhong, Xu; Zou, Jizhao (IOP Publishing, 2019)
Functional modification and structural design of carbon electrode materials are considered as a cost-effective method to improve their electrochemical performance. In this study, a solvothermal method is applied to realize self-assembly of the metal-organic framework. After simple carbonization and acid treatment, carbon nanosheets with 2D adjustable defective sub-units are successfully prepared for the first time. It is found that carbonization temperature has a significant effect on the carbon skeleton structure. The optimal nanostructures with large specific surface area and appropriate pore size distribution make self-assembled carbon nanosheets having excellent Li/Na- ion storage properties. In addition, the adjustable carbon skeleton structure can effectively avoid irreversible damage when charge-discharge cycles. For Li-ion batteries, a specific capacity of 825 mAh g−1 is achieved after 100 cycles at 0.1 C, while for Na-ion batteries a specific capacity of 193 mAh g−1 is observed after 100 cycles at 0.5 C. Moreover, for Na-ion batteries, even at a high rate of 5 C the material delivers a specific capacity of 109.5 mAh g−1 after 3500 cycles.
Keywords: Porous carbon nanosheets; nanostructure; 2D-MOF; Li-ion; Na-ion